Financial Resilience and recovery from inflation shock Report about a Ludovika University Conference - Kutasi, Gábor (Public Finance Quarterly, 2024)
The Faculty of Public Governance and International Relations at Ludovika University has been hosting several conferences attempting to reply for the economics challenges and threats emerged in the recent years. The period 2020-2023 will create a complex situation for financial institutions and businesses worldwide, characterized by increased economic uncertainty and the lagging effects of pandemic COVID-19 and high inflation. In this context, financial resilience refers to the resilience of businesses and economies. Inflation in 2022-2023 has posed significant challenges for both banking and corporate finance.